Enabling Community Participation for Social Innovation in the Energy Sector - Budiman, Ibnu (Indonesian Journal of Energy, 2018)
This study investigates enabling conditions for facilitating social innovation in the energy sector. This aspect is important to support the energy transition in Indonesia. This research provides appropriate project direction, including research (and action) gaps for the energy actors in Indonesia. The actors are encouraged to work further with the result of this study to stimulate the energy transition in Indonesia. This study uses a systemic change framework which recognizes four drivers of systemic change in a region: 1. transforming political ecologies; 2. configuring green economies; 3. building adaptive communities; 4. social innovation. These drivers are interconnected, and this study focuses on how the social innovation can be supported by other drivers. This study used interviews and literature review as the sources of data. There were interviews with eight experts who come from different countries and are experienced in social innovation in the energy sector. Afterward, this research reviewed related journal papers from the last five years, to check the latest developments within the topic, to support the interview results. The study found that the enabling condition can focus on one of the drivers of systemic change, which is building communities by increasing their participation, through several integrated actions. This point can be implemented in two types of citizen energy initiatives which are energy cooperatives and sustainable consumption initiatives. Further implementation of these initiatives requires a study on policy and governance support, to create complete enabling conditions to facilitate social innovation in the energy transition.